The Relationship Between Protein Consumption And Income And The Incidence Of CED In Pregnant Women In The Working Area Of The Lembang Health Center - Nurhijrani, Nurhijrani (Jurnal EduHealth, 2022)
Chronic energy deficiency is one of the malnutrition problems that often occur in pregnant women and is caused by a long-term lack of protein energy. The study's goal was to determine the relationship between protein consumption and income and the incidence of CED in pregnant women in the Lembang Health Center's working area.This study aims to determine the relationship between protein consumption and income and the incidence of CED in pregnant women in the working area of the Lembang Health Center. An analytical survey with a case control (retrospective) design was used in this study.This study analyzed the relationship between risk factors (protein consumption and income) and the incidence of CED in pregnant women in the working area of the Lembang Health Center. According to the results of this study, there is a relationship between protein consumption and the incidence of CED in pregnant women in the working area of the Lembang Health Center with a moderate level of relationship strength, and there is a relationship between family income and the incidence of CED in pregnant women in the Lembang Health Center work area with a weak level of relationship strength. The author's suggestion for the public, especially pregnant women, is that it is hoped that pregnant women can pay attention to and meet their nutritional needs, so that they avoid SEZs and actively seek information and ask lots of questions so they know more about health, especially related to CED problems.